The Englishized Subject Postcolonial Writings in Hong Kong, Singapore and Malaysia - Tam, Kwok-kan.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book addresses issues of how the cultures in Hong Kong, Singapore and Malaysia have been Englishized in postcolonial and globcalized contexts, not just in terms of language, but also in writers'/people's subjectivity. Taking a cultural-literary approach to the study of Englishized subjectivity, the book offers a unique study of hybridized literary/language forms by relating them to bilingual thinking and bicultural sensibility. Poets, novelists and playwrights have different strategies to cope with new images and new forms of expression that can capture their sense of hybridized identity, and as a result, hybridity becomes creativity.
Preface -- Introduction: Englishization and the New Asian Subjectivity -- 1 Post-Imperial/Postcolonial English(es) -- 2 Transnational Shakespeare -- 3 Englishization in Education and (Post/)Colonial Identity in Hong Kong -- 4 Localism in English Language Teaching in Hong Kong -- 5 Identity of the In-Between in Contemporary Hong Kong Literary Writings -- 6 The Self Between Race and Identity: Two Hong Kong Bilingual/Bicultural Plays -- 7 Bilingual Metaphor in Hong Kong and Singapore Writings -- 8 Hybridity in Language and Identity: New Englishes in Hong Kong, Singapore, and Malaysia -- 9 In Between Cultures and Nation: Writing the Self in Singapore -- 10 The Self as Hybrid Contestation: Three Autobiographical Stories from Singapore and Malaysia -- 11 Globalization as Englishization -- Bibliography -- Index.
Keywords: Anthropological linguistics; Economic development; Southeast Asia -- History; Social history; Linguistic Anthropology; Development Studies; History of Southeast Asia; Social History